(3eSGYO GdWdGH aj GdcTa Yf bhGYO GdEYQGHs - (3GdPQhj, fLe GdOjf, GdeQLGfj, GdeQLGfj, eMeO Hf CHj HcQ Hf Ydj, fLe GdOjf, J (B827(3g` (B1424(3es ((3MSf Hf Ydj GdeQOGhjs)
(3ChdgG (B:s
(3ChdgG(B: (3bGd eMeO gh GdeQLGfj (B*** (3CMeO QHj NGdb GdEfSGf (B. (3GYde Cf GdcdGe gh GddaX GdeajO HGdbUO hGdeQGO HGdeajO eG Od Ydi eYfi jMSf GdSchJ Ydjgs
(3BNQgG (B:s
(3BNQgG(B: (3hWGhjGf hWhi eLghd Whi, aEfg dh CYd GdhGh ajgeG dbdH GdaGA hHEScGfgG djfbd GdcSQI YdjgG de jdRe GLeGY (B... (3hGdMeO ddg Ydi GdJeGe hYdi QShdg CaVd GdUdGI hGdSdGes
(3cJH GedGA ef GdeUfas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 57s
(3EjVGM Gdecfhf, L (B2: 472s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdfMhs